Formalization of the Procedure for Managing the Property Complex of the University - Sadikova Sh. Sh. (International Journal on Integrated Education, 2022)
In accordance with the method of analysis of hierarchies, the ranking of property management performance indicators into a hierarchical set containing 4 levels was carried out: goal, groups of indicators, indicators, factors. The procedure for managing the university's property complex has been formalized and the parameters of a rational solution to the set management problem have been identified. The conceptual structure of the decision support system for managing the university's property complex has been built. A functional model of the system has been developed. The projected decision support system includes the following subsystems: a subsystem for processing expert opinions, a subsystem for generating accounting data for fixed assets, a subsystem for making decisions on the effectiveness of university property management.